2011
DOI: 10.1088/1742-6596/324/1/012017
|View full text |Cite
|
Sign up to set email alerts
|

Spin relaxation in Kondo lattices

Abstract: A model of spin relaxation in Kondo lattices is proposed to explain the presence of an electron spin resonance (ESR) signal in the heavy fermion compounds YbRh 2 Si 2 and YbIr 2 Si 2 . Coupled equations for dynamical susceptibilities of Kondo ions and conduction electrons are derived by means of the functional derivative method. The perturbational scaling approach reveals the collective spin motion of Yb-ions with conduction electrons in the bottleneck regime. A common energy scale due to the Kondo effect regu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…YbRh 2 Si 2 and YbIr 2 Si 2 belong to the class of heavy-fermions Kondo-lattice compounds which attracted the interest of scientists due to the very peculiar magnetic, thermal and transport properties. The discovery of electron paramagnetic resonance (EPR) in the Kondo lattices YbRh 2 Si 2 and YbIr 2 Si 2 below the thermodynamically measured Kondo temperatures was very unexpected [1][2][3] and stimulated different approaches for its explanation [4][5][6][7]. In particular, in [6,7] is shown that the idea of a collective spin motion of quasi-localized Yb f-electrons and wide-band electrons successfully explains the EPR signal existence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…YbRh 2 Si 2 and YbIr 2 Si 2 belong to the class of heavy-fermions Kondo-lattice compounds which attracted the interest of scientists due to the very peculiar magnetic, thermal and transport properties. The discovery of electron paramagnetic resonance (EPR) in the Kondo lattices YbRh 2 Si 2 and YbIr 2 Si 2 below the thermodynamically measured Kondo temperatures was very unexpected [1][2][3] and stimulated different approaches for its explanation [4][5][6][7]. In particular, in [6,7] is shown that the idea of a collective spin motion of quasi-localized Yb f-electrons and wide-band electrons successfully explains the EPR signal existence.…”
Section: Introductionmentioning
confidence: 99%
“…The discovery of electron paramagnetic resonance (EPR) in the Kondo lattices YbRh 2 Si 2 and YbIr 2 Si 2 below the thermodynamically measured Kondo temperatures was very unexpected [1][2][3] and stimulated different approaches for its explanation [4][5][6][7]. In particular, in [6,7] is shown that the idea of a collective spin motion of quasi-localized Yb f-electrons and wide-band electrons successfully explains the EPR signal existence. In [8] the static magnetic susceptibility of YbRh 2 Si 2 and YbIr 2 Si 2 were also successfully studied, based on entirely local properties of Yb 3+ ions in a tetragonal crystal electric field (CEF).…”
Section: Introductionmentioning
confidence: 99%
“…To consider the spin dynamics in the Kondo lattice under discussion we use the model including the kinetic energy of conduction electrons, the Zeeman energy, the Kondo interaction between Yb ions and conduction electrons, and the coupling between the Yb ions via conduction electrons (RKKY interaction) [23][24][25][26][27][28][29][30]. The physics of lowenergy spin excitations at temperatures 200 K T  can be described by the lowest Kramers doublet.…”
Section: Theoretical Modelmentioning
confidence: 99%
“…σσ σσ Γ = Σ Calculations of these coefficients up to the third order in the Kondo interaction give [24] ( )…”
Section: Spin Dynamicsmentioning
confidence: 99%
“…The discovery of electron spin resonance (ESR) in the Kondo lattice YbRh 2 Si 2 below the Kondo temperature T K ≈ 25 K [1] (T K revealed by specific heat data [2] and by transport measurements [3]) was a great surprise to the condensed matter physics community and stimulated different approaches for its explanation [4][5][6][7][8]. According to the picture based on the single ion Kondo effect, the magnetic moments of the Yb ions are screened by conduction electrons at T < T K and the ESR linewidth is of the order ν = k B T K /2π h = 500 GHz.…”
Section: Introductionmentioning
confidence: 99%